2017
DOI: 10.1007/s40750-017-0067-y
|View full text |Cite
|
Sign up to set email alerts
|

‘Naltrexone Blocks Endorphins Released when Dancing in Synchrony’

Abstract: Group synchronised dance is hypothesised to activate the Endogenous Opioid System (EOS), thereby increasing pain threshold, and encouraging social closeness. Previous studies have been limited to the use of pain threshold as a proxy indicator of EOS activation. We conducted a double-blind administration of placebo and naltrexone (an endorphin antagonist) before groups of strangers danced in synchrony and measured both pain threshold and sense of belonging to the group after dancing. A 100 mg dose of naltrexone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 95 publications
2
42
0
Order By: Relevance
“…The effect of naltrexone on self-reported feelings of social connection to social and physical warmth resulted in a pattern consistent with hypotheses but was not statistically significant. Indeed, the effect of naltrexone on feelings of social connection shows mixed results with some studies showing a statistically significant reduction (Inagaki et al, 2015; Inagaki et al, 2016a), some showing no effect (Tarr et al, 2017) and some showing an effect only after considering moderators (Depue and Morrone-Strupinsky, 2005). Similarly, holding a warm vs a cool object did not increase VS and MI activity corrected at the whole brain in the placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of naltrexone on self-reported feelings of social connection to social and physical warmth resulted in a pattern consistent with hypotheses but was not statistically significant. Indeed, the effect of naltrexone on feelings of social connection shows mixed results with some studies showing a statistically significant reduction (Inagaki et al, 2015; Inagaki et al, 2016a), some showing no effect (Tarr et al, 2017) and some showing an effect only after considering moderators (Depue and Morrone-Strupinsky, 2005). Similarly, holding a warm vs a cool object did not increase VS and MI activity corrected at the whole brain in the placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…For example, social laughter [57], music performance [58], viewing of emotionally engaging movies [59] and rowing with others [60] elevate pain threshold, suggesting that various forms of social affiliation induce enhanced opioidergic processing in humans. While the evidence from these studies is indirect, it has also been shown that the dance-induced elevation of pain threshold can be blocked with naltrexone-pretreatment [61]. This finding suggests that opioidergic activity indeed contributes to the analgesic effect of affiliation.…”
Section: Human Opioid System Responds To Social Activitiesmentioning
confidence: 96%
“…In order to be able to increase group size, humans discovered how to exploit other behaviours that also trigger the endorphin system in a way that is, in effect, a form of grooming-at-a-distance. These include laughter [ 109 ], singing [ 110 ], dancing [ 111 ], emotional storytelling [ 112 ], and communal eating [ 113 , 114 ] and drinking (of alcohol) [ 115 ], all of which trigger the endorphin system and do so incrementally when done in synchrony [ 116 , 117 ]. Because they do not involve direct physical contact, more individuals can be ‘groomed’ simultaneously, thereby allowing a form of time-sharing that makes it possible to reach more individuals and so increase group size.…”
Section: Time Trust and The Bonds That Bindmentioning
confidence: 99%